Towards a taxonomy of innovation systems - Godinho, Manuel Mira (2005)
The concept of National Innovation System (NIS) has been recently applied in the context of developing nations even tough it was originally developed in relation to the more developed economies (Japan, Scandinavian countries, US etc.). This raises the methodological problem of knowing whether what was learnt in the study of more advanced NISs is relevant for all sorts of economies regardless the maturity of their actual innovation systems. With this question in mind an exploratory exercise is implemented. First a technique for mapping different NIS is put forward and next based on such mapping a taxonomy of NISs is proposed. The technique although simple in the steps it requires shows analytical potential. The cartography it generates allows one to compare directly different countries, by visualizing in bi-dimensional space the graphic pattern of the relevant dimensions of their respective NISs. This technique is applied to 69 countries (87.4% of the world population) and a set of 29 indicators is used to examine these NISs along eight major dimensions. With the resulting data, and with the help of cluster analysis, a taxonomy of innovation systems is proposed. That taxonomy which contains 6 major types of NISs indicates that what differentiates most the individual systems is their performance in three critical dimensions: innovation, diffusion and basic and applied knowledge. Country size and the natural resources endowment of the economies also emerge as important contingency factors underlying the overall dynamics of different NISs.